Genetic Diversity of Ostreopsis ovata (Dinophyceae) from Malaysia - Leaw, C. P.; Lim, P.T.; Asmat, Ahmad; Usup, G. (Springer-Verlag, 2001)
The genus Ostreopsis is an important component of benthic and epiphytic dinoflagellate assemblages in coral reefs and seaweed beds of Malaysia. Members of the species may produce toxins that contribute to ciguatera fish poisoning. In this study, two species have been isolated and cultured, Ostreopsis ovata and Ostreopsis lenticularis. Analyses of the 5.8S subunit and internal transcribed spacer regions ITS1 and ITS2 of the ribosomal RNA gene sequences of these two species showed that they are separate species, consistent with morphological designations. The nucleotide sequences of the 5.8S subunit and ITS1 and ITS2 regions of the rRNA gene were also used to evaluate the interpopulation and intrapopulation genetic diversity of O. ovate found in Malaysian waters. Results showed a low level of sequence divergence within populations. At the interpopulation level, the rRNA gene sequence distinguished two groups of genetically distinct strains, representative of a Malacca Straits group (isolates from Port Dickson) and a South China Sea group (isolates from Pulau Redang and Kota Kinabalu). Part of the sequences in the ITS regions may be useful in the design of oligonucleotide probes specific for each group. Results from this study show that the ITS regions can be used as genetic markers for taxonomic, biogeographic, and fine-scale population studies of this species.